PENGARUH FASILITAS PAJAK, TINGKAT UTANG, DAN KOMPENSASI MANAJEMEN TERHADAP MANAJEMEN PAJAK - -, Yulyanah; Awaludin, Rahmat (Jurnal Ilmiah Publika, 2023)
This study aims to empirically prove the effect of tax facilities, debt levels, and management compensation on tax management. This research was conducted in Energy Sector companies listed on the Indonesia Stock Exchange. The type of research used is quantitative. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) during 2017-2021. Samples were collected using purposive sampling method in order to obtain as many as 85 observational data. The data was processed using the Eviews 10 Statistical Program to test the hypothesis using panel data regression analysis. Based on the results of the F statistical test simultaneously tax facilities, debt levels, and management compensation together have an influence on tax management. The results of the t statistical test partially tax facilities and management compensation have an influence on tax management. While the level of debt has no effect on tax management.